Learning Concurrency in Kotlin - Miguel Angel Castiblanco Torres (Packt Publishing, 2018)
Concurrency is a critical component of modern app development, and Kotlin's approach offers powerful tools for this domain. "Learning Concurrency in Kotlin" provides step-by-step guidance on writing concurrent, efficient, and scalable applications using Kotlin's unique coroutine system. With practical examples and expert insights, this book covers everything a developer needs.What this Book will help me doUnderstand the core concepts of Kotlin's coroutines for writing non-blocking concurrent programs.Learn to design efficient data pipelines and implement asynchronous tasks effectively.Master the handling of exceptions and errors in a concurrent Kotlin application.Explore advanced patterns using channels for inter-coroutine communication.Apply acquired knowledge to build real-world applications like an Android RSS reader.Author(s)None Castiblanco Torres is an experienced Kotlin and Android developer with a deep understanding of concurrency concepts. They have dedicated their career to mastering software scalability and efficiency and have authored impactful resources for developers. Through a practical and concise writing style, None aims to share their knowledge with learners in an accessible manner.Who is it for?This book is ideal for Kotlin and Android developers wanting to learn and apply concurrency to their projects. Readers should have a basic understanding of programming concepts in Kotlin or Java. You may have worked on mobile or server-side applications and are looking to optimize performance. If you're eager to enhance your expertise in modern concurrency techniques, this book is for you.